2008
DOI: 10.4055/jkoa.2008.43.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Late Presented Displaced Lateral Condylar Fracture of the Humerus in Children

Abstract: 지연 발현된 전위된 소아 상완골 외과 골절의 수술적 치료 배기철ㆍ송광순ㆍ강철형ㆍ민병우ㆍ조철현ㆍ사공협 계명대학교 의과대학 동산의료원 정형외과학교실Purpose: To determine whether late open reduction and internal fixation (ORIF) of a lateral condylar fracture (LCF) after 3 weeks is possible, and to determine the latest time for ORIF without a bone graft. Materials and Methods: Eight children underwent late ORIF (>3 weeks) of a displaced LCF (>2.5 mm) of the humerus between 3 weeks and 5 weeks after injury. Results: Clinically, results were excellent in 6 cases and good in 2 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Compared to K C Bae [13] study the average age of the patients in our study was higher, and we observed satisfactory results of late open reduction even at higher mean age of patients and more delayed presentation of fractures compared to his study. The overall satisfactory results of patients in our study compared to K C Bae's study could be attributed to the modification of surgical technique, respecting the local biology of the fracture, and use of bone graft in fractures presenting more than six weeks after the injury.…”
Section: Mode Of Injurycontrasting
confidence: 58%
“…Compared to K C Bae [13] study the average age of the patients in our study was higher, and we observed satisfactory results of late open reduction even at higher mean age of patients and more delayed presentation of fractures compared to his study. The overall satisfactory results of patients in our study compared to K C Bae's study could be attributed to the modification of surgical technique, respecting the local biology of the fracture, and use of bone graft in fractures presenting more than six weeks after the injury.…”
Section: Mode Of Injurycontrasting
confidence: 58%
“…Delayed LCFH in children is not common, and only a few case series have been reported [ 4 , 5 , 12 , 13 ]. Besides, the optimal choice of treatment for this condition remains controversial [ 2 , 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the optimal choice of treatment for this condition remains controversial [ 2 , 3 , 8 ]. The conservative method possibly results in poor clinical outcomes, including pain, instability of elbow joint, cubitus valgus deformity, and resultant ulnar nerve palsy [ 3 5 , 12 ]. However, surgical intervention carries a potential risk of AVN, infection, stiffness of the joint, and growth disturbance of distal humerus [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation